Prevalence of Parasitic Species in Ruminants Found in the Vicinity of Lahore, Pakistan - Rafi, Uzma; Yasmeen, Roheela; Qureshi, Aisha Waheed; Bukhari, Rabia; Bukhari, Syeda Shazia (Scientific Inquiry and Review, 2021)
In Pakistan, the livestock industry is one of the most important subsectors of the agricultural industry since it offers a handsome share in gross domestic national growth. However, gastrointestinal parasitic infections are a serious health concern for cattle managing organizations and farmers. The effects of gastrointestinal parasites may vary with the age, sex of cattle, nutritional practices, and the severity of contagion. For this reason, there is a need to update the knowledge on spatio-temporal differences and regulate practices to improve the health conditions of animals. The current study aimed to estimate the prevalence of gastrointestinal parasites in bovine, caprine and ovine genera reared in and around Lahore. A total number of 160 fecal samples were collected from the selected genera. To calculate the prevalence of parasites in different genera, all samples were subjected to parasitological examination and analyzed using the direct smear method. In general, an overall prevalence of 40% was recorded which showed 64 samples were positive. The observed parasitic species were Balantidium coli (a parasitic protozoan), Fasciola hepatica (liver fluke), Coccidia (a microscopic protozoan), Shistosoma bovis (blood fluke), Ostertagia ostertagi (parasitic nematode), Trichuris globulosa (intestinal nematode), Haemonchus contortus (pathogenic nematode), Chabertia ovina (parasitic roundworms), and Strogyloides papillosus (parasitic nematode). Overall, out of 160 total samples, 64 samples were positive, while 40% prevalence was recorded in all ruminants. Among bovines, (cows and buffaloes), the multi-parasites prevalence was recorded to be 47.5 and 37.5%, respectively. However, in ovine (sheep) and caprine (goats), the prevalence was 42.5 and 32.5%, respectively. The parasitic prevalence was observed alike in adults and young. The data showed a higher parasitic prevalence in adult bovine and ovine species as compared to the caprine species. The study revealed that there is a significant difference in prevalence (P value< 0.05) between adult and young buffaloes having Balantidium coli, cows having Fasicola hepatica, and goats having Ostertagia ostertagi. Additionally, it was concluded that the low occurrence of parasites in ovine and caprine species as compared to bovine species was due to the use of proper care and deworming practices. Moreover, different managerial control practices and awareness programs also need to be implemented to control gastrointestinal parasitic infections. Keywords: fecal samples, direct smear method, parasites, prevalence Copyright(c) The Authors